The impact of dormitory atmosphere on academic performance in medical university: a cross-sectional study - Xu, Ying; Xu, Rujing; Wu, Junjie; Wen, Yuehan; Xu, Nuo; Gao, Yiwen; Liang, Zixin; Wang, Jianzhong; Hu, Jie; Wu, Xiaqiu; Wang, Binyan; Fang, Jing (Frontiers in Psychology, 2025)
IntroductionAcademic performance (AP) serves as a comprehensive measure of students’ academic proficiency and learning status, while dormitory atmosphere plays a significant role in shaping students’ daily lives. This study investigated the impact of dormitory atmosphere on the AP of college students.MethodsA questionnaire-based survey was conducted at Zhejiang Chinese Medical University, incorporating the grade point average (GPA) of each participant as part of the research data. The study included 601 participants.ResultsThe study found that dormitory hygiene and dormitory interpersonal atmosphere were significantly correlated with AP (OR = 0.54, 95% CI [0.36, 0.83], p = 0.004; OR = 1.60, 95% CI [1.10, 2.31], p = 0.014), whereas the dormitory academic atmosphere within the dormitory showed no significant association (OR = 0.91, 95% CI [0.62, 1.33], p = 0.624). Subgroup analysis revealed that dormitory hygiene (OR = 2.86, 95% CI [1.70, 4.82], p < 0.001) and dormitory interpersonal atmosphere (OR = 0.41, 95% CI [0.25, 0.66], p < 0.001) significantly influenced AP among female students, whereas no significant effects were observed in male students.DiscussionThese findings provide valuable insights into factors influencing AP and offer guidance for creating a supportive dormitory environment for college students.